Hypertrophic cardiomyopathy with mid-ventricular obstruction and apical aneurysm - N.D. Oryshchyn; Yu.A. Ivaniv; Yu.H. Kyjak; S.S. Pavlyk; V.S. Moroz; D.I. Besh; I.M. Bigun (Кардіохірургія та інтервенційна кардіологія, 2016)
A case report of apical left ventricular aneurysm in patient with hypertrophic cardiomyopathy with mid-ventricular obstruction (diagnosis and surgical treatment) is presented. We revealed apical aneurysm and mid-ventricular obstruction during echocardiography and specified anatomical characteristics of aneurysm during computer tomography. There was no evidence of obstructive coronary artery disease during coronary angiography. Taking into consideration multiple cerebral infarcts, aneurysm resection and left ventricular plastics was performed. Electronic microscopy of myocardium confirmed the diagnosis of hypertrophic cardiomyopathy.